Harsh parenting in high socioeconomically disadvantaged families : family predictors and the effectiveness of an attachment-based intervention program - Pereira, Mariana Monteiro de Aguiar (2013)
Tese de doutoramento em Psicologia (área de especialização de Psicologia Clínica)